Towards normatively limited judicial sanction [structured discretion] as a proportional response to the defectiveness of legal action (contract) in modern legal transactions (Studia Prawnicze / The Legal Studies, 2019)
The primary purpose of the legal considerations herein is to indicate the direction of the modernization of the legality of control mechanisms in modern legal transactions.At the base of these transactions there is still the traditional, dogmatic sanction of nullity (invalidity) regulated by law (ex lege), and the legal effects of a defective legal action (contract), i.e. an action contrary to law or moral norms. In consideration of disproportionality and ineffectiveness of the nullity sanction under new conditions, jurisprudence and legislation have directed their attention to the limited judicial sanction (structured discretion) originating from the common law tradition as a proportional and flexible response to the defectiveness of legal action (contract). The statutory judicial sanction, which became the basis of the reform on the concept of illegality in common law countries, have found expression in the model rule of European private law. The Principles of European Contract Law (PECL) and the Draft Common Frame of Reference (DCFR), the latter of which revises and updates the PECL, are the primary references for the model rules of contract law in the EU. The PECL and the DCFR have affected the concept of the defective sanction of legal action (contract) in the new Civil Code, drafted by the Polish Civil Law Codification Commission.